Graphene reinforced AlNiTiCrNbx high entropy alloy coatings by laser additive manufacturing and its application in automatic surveying robot - Chunge Liu; Xingwu Qiu; Qian Su; Yongqiang Shen; Zhansheng Wang; Jia Peng; Zhongwei Liu (Journal of Materials Research and Technology)
Automatic surveying robots serve as critical tools for replacing manual labor and enhancing efficiency in surveying tasks. However, the aluminum (Al) alloy surfaces of these robots are prone to wear and corrosion during operation. To solve the problem, improve the surface condition of the Al alloy, achieve its normal use and extend its service life, this study adopts a laser additive manufacturing technology to prepare graphene (Gr) reinforced AlNiTiCrNbx (x = 0.15, 0.3, 0.45, 0.60) high entropy alloys (HEAs) composite coatings on the Al alloy substrate. The preparation parameters were optimized through orthogonal experiments. The effects of Nb content on the microstructure, mechanical properties and corrosion resistance of the coatings were systematically investigated, the influence of Gr on the coating was also studied. The microstructure of the coatings were analyzed using XRD, SEM, TEM, etc. The electrochemical corrosion resistance and mechanical properties of the coatings were studied using an electrochemical workstation, hardness tester, and friction and wear tester. The results indicate that the Gr/AlNiTiCrNbx coatings primarily consist of fine equiaxed crystals, with both Gr and Nb contributing to grain refinement. With increasing Nb content, the coating microhardness increases, while both wear and corrosion resistance exhibit an initial improvement followed by deterioration. The coatings exhibit outstanding mechanical and anti-corrosion properties, achieving a maximum microhardness of 491 HV, a minimum average friction coefficient of 0.40, and a corrosion current density as low as 6.73 × 10−5. Practical applications confirm that the Gr/AlNiTiCrNbx coatings significantly enhance the durability and operational lifespan of automatic surveying robots.